Evaluating change in English language teaching - Lamie, Judith (Houndmills, Basingstoke, Hampshire ; New York : Palgrave MacMillan, 2005)
'This book, written by an experienced teacher-trainer and teacher, is intended to be of interest and use to teacher-trainers and teachers, to curriculum developers and planners, to those who co-ordinate and manage English teaching, and to the less experienced, such as teacher-trainees. This book aims to examine the theory and practice of change; setting the theory in its educational context by providing references to contemporary research and case studies in the English language teaching and Applied Linguistic context.'--BOOK JACKET.
Includes bibliographical references (p. 237-248) and indexes.
Keywords: English language -- Study and teaching -- Foreign speakers -- Evaluation; Educational change